Perpajakan terhadap Kepatuhan Wajib Pajak - Latifah Latifah (Jurnal Maksipreneur, 2013)
This paper examines the effect of tax system quality, audit risk, accountability, and tax penalty towards tax compliance. The purpose of this paper is to seek empirical proof does those factors affecting tax compliance have a positive effect and play a significant role for individual tax compliance in Indonesia. The researcher decides to sample taxpayers working for Organisasi Kelompok Kontrak Kerjasama (KKKS) in BPMIGAS Indonesia. A survey questionnaire is distributed to the sample during October 2012 by email as research data. By employing simple descriptive statistics, the study on taxpayers working for BPMIGAS Indonesia found out that all variables: tax system quality, audit risk, accountability, and tax penalty shows a positive effect towards tax compliance. The findings of this research implied that the government should put more concern in terms or service quality, transparency, and tax related facts to be informed for individual taxpayers.